2013
DOI: 10.1088/0004-637x/775/1/72
|View full text |Cite
|
Sign up to set email alerts
|

The Gravitational Drag Force on an Extended Object Moving in a Gas

Abstract: Using axisymmetrical numerical simulations, we revisit the gravitational drag felt by a gravitational Plummer sphere with mass M and core radius R s , moving at constant velocity V 0 through a background homogeneous medium of adiabatic gas. Since the potential is non-diverging, there is no gas removal due to accretion. When R s is larger than the Bondi radius R B , the perturbation is linear at every point and the drag force is well fitted by the time-dependent Ostriker's formula with r min = 2.25R s , where r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Within this linear approximation, the collisional drag force is significantly higher for perturbers moving with Mach numbers 0.7 < M < 2. A similar trend is also seen, in numerical simulations, for low mass, extended, perturbers (Sánchez-Salcedo & Brandenburg 1999;Kim & Kim 2009;Bernal & Sánchez-Salcedo 2013). Importantly, however, these works show the force from the wake is only accurately predicted under certain conditions.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Within this linear approximation, the collisional drag force is significantly higher for perturbers moving with Mach numbers 0.7 < M < 2. A similar trend is also seen, in numerical simulations, for low mass, extended, perturbers (Sánchez-Salcedo & Brandenburg 1999;Kim & Kim 2009;Bernal & Sánchez-Salcedo 2013). Importantly, however, these works show the force from the wake is only accurately predicted under certain conditions.…”
Section: Introductionsupporting
confidence: 73%
“…Any scenario can be completely described by two parameters: this 𝐴 parameter, and the Mach number M of the perturber moving through the gaseous background medium. The predicted force, give by Equations (3), (4) and ( 5), has been used to test numerical results, and they were found to match for suitably chosen 𝐴 and 𝑟 min (Sánchez-Salcedo & Brandenburg 1999;Kim & Kim 2009;Bernal & Sánchez-Salcedo 2013). As discussed in Section 1, these works find the forces match for when 𝑟 min has certain values.…”
Section: Linear Wakementioning
confidence: 92%
See 2 more Smart Citations
“…where r max 2.1 √ 2H and r min is the minimum impact parameter for the interaction. In the case of a Plummer perturber with R soft > R acc , Bernal & Sánchez-Salcedo (2013) found that r min = 2.25R soft (see also Sánchez-Salcedo & Brandenburg 1999). Putting together, the predicted torque on a softened body having R acc < R soft H, on a retrograde circular orbit, is…”
Section: Analytical Predictionsmentioning
confidence: 91%